Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 43627 species occurrences available in GBIF matching the query: { "and" : [ "Country is Colombia", "HasGeospatialIssue is false", "Geometry POLYGON((-74.66 4.90,-74.66 5.45,-73.80 5.45,-73.80 4.90,-74.66 4.90))" ] } The dataset includes 43627 records from 118 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006103-160803222355964/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences